Kualitas Air Budidaya Ikan Koi (Cyprinus Rubrofuscus) pada Sistem Vertiqua Menggunakan Filter Biofikal Atas - Ikhsan Kamil; Ujang Dindin; Novita MZ (Habitat: Jurnal ilmiah ilmu Hewani dan Peternakan, 2024)
Land and water sources are important in cultivation activities. Efforts to overcome the problem of limited land and water for cultivation include technology development. One of the technologies being developed is vertiqua. The Vertiqua that has been developed, both with and without biophysical filters, still has weaknesses, namely high levels of ammonia. Therefore, a biofical modification was carried out, namely using a biofical top filter to increase the effectiveness of reducing ammonia levels to support fish growth in the vertiqua. The aim of this research was to test the effectiveness of the biofical top filter on the rate of reduction in ammonia levels in the vertiqua. The research design was carried out using a Completely Randomized Design (CRD) for one treatment with three repetitions, in this study with an upper biophysical filter as treatment and three vertiquas as repetitions. The data analysis carried out in this research was an experimental method. The results of the research are presented in the form of graphs, tables and narratives using Microsoft Word and Excel. As for testing, the research sample was tested with the middle value using Microsoft Excel and Minitab 21 by comparing the test results with the standard. According to the research results, the use of an upper biophysical filter can have an effect on maintaining physical and chemical water quality parameters (P<0.05) so that they comply with quality standards. However, there are several water quality parameters that do not comply with quality standards, such as pH and nitrite. The use of the upper biophysical filter type in the vertiqua koi fish cultivation system has an effect on reducing ammonia and maintaining water quality so that it meets quality standards. However, the nitrite value at the beginning was high, but after two weeks of testing the value began to decrease, indicating that the upper biofical filter was running optimally.